Digital Literacy in Elementary School Students: A Systematic Analysis of Trends, Challenges, and Learning Implications - Kukuh Suryo Atmojo; Alfi Laila; Mauludia Kurota’ini; Yuliana Melindawati (Elementary Education Journal, 2025)
Background: Digital literacy has become a crucial competency in primary education along with the development of digital technology. This study aims to analyze development trends, implementation challenges, and implications of digital literacy learning in primary schools for the 2016-2026 period. Method: The study used the Systematic Literature Review (SLR) method with PRISMA 2020 guidelines. A literature search was conducted through the Scopus database and yielded 72 articles during the identification stage. After a selection, screening, and quality assessment process using the QQM Checklist, 17 articles were obtained and analyzed narratively and thematically. Result: The results of the study show three main findings. First, the implementation of digital literacy in primary schools is dominated by the use of innovative technologies such as Augmented Reality, gamification, virtual field trips, stop-motion, and creative videomaking, which have been proven to increase student engagement and digital competence. Second, teachers' digital competence is a key factor in the success of technology integration, but still faces various obstacles such as low pedagogical readiness, gaps in technology access, and limitations in adaptive technology use. Third, the concept of digital literacy is evolving from merely technical skills to critical-reflective, social-emotional, digital health, and digital citizenship dimensions. Implication: This research implies the importance of systematic digital literacy integration in the elementary school curriculum, strengthening contextual and sustainable teacher professional development programs, and inclusive and equitable education digitalization policies. Novelty: Unlike prior reviews that focus on higher education or discuss elementary school technology use only in general terms, this study offers an SLR specifically on elementary digital literacy, jointly mapping trends, challenges, and implications through rigorous quality appraisal (QQM Checklist).